Ancient and Modern Geochemical Signatures in the 13,500-Year Sedimentary Record of Lake Cadagno - Berg, Jasmine S.; Lepine, Mathilde; Laymand, Emile; Han, Xingguo; Vogel, Hendrik; Morlock, Marina A.; Gajendra, Niroshan; Gilli, Adrian; Bernasconi, Stefano M.; Schubert, Carsten J.; Su, Guangyi; Lever, Mark A. (Frontiers in Earth Science, 2022)
Although lake sediments are globally important organic carbon sinks and therefore important habitats for deep microbial life, the deep lacustrine biosphere has thus far been little studied compared to its marine counterpart. To investigate the impact of the underexplored deep lacustrine biosphere on the sediment geochemical environment and vice versa, we performed a comprehensive microbiological and geochemical characterization of a sedimentary sequence from Lake Cadagno covering its entire environmental history since formation following glacial retreat. We found that both geochemical gradients and microbial community shifts across the ~13.5 kyr subsurface sedimentary record reflect redox changes in the lake, going from oxic to anoxic and sulfidic. Most microbial activity occurs within the top 20 cm of sediment, where millimolar sulfate concentrations diffusing in from the bottom water are almost completely consumed. In deeper sediment layers, organic carbon remineralization is much slower but microorganisms nonetheless subsist on fermentation, sulfur cycling, metal reduction, and methanogenesis. The most surprising finding was the presence of a deep, oxidizing groundwater source. This water source generates an inverse redox gradient at the bottom of the sedimentary sequence and could contribute to the remineralization of organic matter sequestered in the energy-limited deep subsurface.